2021
DOI: 10.21608/adjg.2021.28468.1246
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Chitosan as Final Irrigating Solution on TGF-β1 Release from Root Canal Dentin and its Effect on Dental Pulp Stem Cells Response

Abstract: Purpose: To study the effect of Chitosan final irrigating solution compared with EDTA using different irrigation techniques, on TGF-β1 release from root canal dentin, using enzyme-linked immunosorbent assay (ELISA), and to evaluate the effect of released TGF-β1 on Dental Pulp Stem Cells. Materials and Methods: Human DPSCs were isolated from impacted third molars. Forty eight human root segments were prepared to a standardized truncated cone-shaped canal with an open apex of 1 mm diameter, the volume of prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…TGF-β1 was quantified using ELISA following the canal irrigation procedure. This approach aligns with prior research, as measuring growth factors post-irrigation mirrors the clinical scenario where bleeding is induced at the apex after irrigation and drying [ 6 , 14 , 45 ]. This differs from the study by Galler et al, where growth factor release was measured during irrigation [ 10 ].…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…TGF-β1 was quantified using ELISA following the canal irrigation procedure. This approach aligns with prior research, as measuring growth factors post-irrigation mirrors the clinical scenario where bleeding is induced at the apex after irrigation and drying [ 6 , 14 , 45 ]. This differs from the study by Galler et al, where growth factor release was measured during irrigation [ 10 ].…”
Section: Discussionmentioning
confidence: 63%
“…On the other hand, in the EDTA/DW/XP group, the positive effect of the EDTA activation using the XP-endo Finisher can be attributed to enhanced smear layer removal and thereby reaching inaccessible areas while preserving dentin. Moreover, the XP-endo Finisher has improved irrigation dynamics as the file exhibits increased flexibility and enhanced expansion capacity which leads to the improvement of the penetration of the irrigant into the dentinal tubules [ 45 ]. The increase in the TGF-β1 release in the EDTA/DW/XP group is in accordance with studies that showed that irrigation activation increases the growth factor release from dentin [ 7 , 13 , 34 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations